Analisis Komparatif terhadap Tingkat Pemahaman Peserta Didik Terhadap Proses Pembelajaran - Regina Pandia; Nova Purba; Ema Linda Lumban Gaol; Fanny Puspasari Br Sianipar; Rohana Rohana (Pancasila and Civics Education Journal, 2026)
Abstract: This research aims to analyze and compare student understanding during the learning process at SMA Negeri 1 Rantau Utara and SMA Negeri 1 Rantau Selatan. The study used an observational qualitative approach to obtain an in-depth picture of the level of student understanding during the learning process. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate differences in student understanding at the two schools. These differences are influenced by variations in learning methods applied by teachers, the level of student involvement in learning activities, and the availability and utilization of learning facilities. The novelty of this study lies in the comparative analysis conducted through direct observation of student understanding in two different school contexts. The research findings are expected to serve as evaluation material and considerations for schools in improving the quality of the learning process and student understanding.Keywords: Student Understanding, Learning Process, Comparative Study, Qualitative ResearchAbstrak: Penelitian ini bertujuan untuk menganalisis dan membandingkan pemahaman peserta didik dalam proses pembelajaran di SMA Negeri 1 Rantau Utara dan SMA Negeri 1 Rantau Selatan. Penelitian menggunakan pendekatan kualitatif observatif untuk memperoleh gambaran yang mendalam mengenai tingkat pemahaman peserta didik selama mengikuti pembelajaran. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Data dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan adanya perbedaan pemahaman peserta didik pada kedua sekolah. Perbedaan tersebut dipengaruhi oleh variasi metode pembelajaran yang diterapkan guru, tingkat keterlibatan peserta didik dalam kegiatan belajar, serta ketersediaan dan pemanfaatan fasilitas pembelajaran. Kebaruan penelitian ini terletak pada analisis komparatif yang dilakukan melalui observasi langsung terhadap pemahaman peserta didik pada dua konteks sekolah yang berbeda. Temuan penelitian diharapkan dapat menjadi bahan evaluasi dan pertimbangan bagi sekolah dalam meningkatkan kualitas proses pembelajaran serta pemahaman peserta didik.Kata Kunci: Pemahaman Siswa, Proses Pembelajaran, Studi Perbandingan, Penelitian Kualitatif